(untitled) - Mercer, William (Arlington, Massachusetts, 1999)
This glorious photographie essay by William Mercer captures the vibrancy of Simmons today and confirms its place in the future.
Keywords: Trường Cao đẳng Simmons,Simmons College (Boston, Mass.)